2005
DOI: 10.1038/sj.gt.3302593
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer into human hematopoietic progenitor cells with an episomal vector carrying an S/MAR element

Abstract: Episomally maintained self-replicating systems present attractive alternative vehicles for gene therapy applications. Recent insights into the ability of chromosomal scaffold/ matrix attachment regions (S/MARs) to mediate episomal maintenance of genetic elements allowed the development of a small circular episomal vector that functions independently of virally encoded proteins. In this study, we investigated the potential of this vector, pEPI-eGFP, to mediate gene transfer in hematopoietic progenitor cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 43 publications
9
85
0
3
Order By: Relevance
“…Minicircles containing an SV40 origin of replication and an SMAR were not episomally replicative following partial hepatectomy in the current study. These data are in line with observations of Papapetrou et al 45 who showed that 4 weeks after transduction of human hematopoietic progenitor cells with a plasmid containing an SMAR, DNA was retained in less than 1% of the transduced cells. In contrast, mitotic stability of an episomal vector containing a human SMAR has been shown in in vitro studies.…”
Section: Adenoviral and Hydrodynamic Transfersupporting
confidence: 81%
“…Minicircles containing an SV40 origin of replication and an SMAR were not episomally replicative following partial hepatectomy in the current study. These data are in line with observations of Papapetrou et al 45 who showed that 4 weeks after transduction of human hematopoietic progenitor cells with a plasmid containing an SMAR, DNA was retained in less than 1% of the transduced cells. In contrast, mitotic stability of an episomal vector containing a human SMAR has been shown in in vitro studies.…”
Section: Adenoviral and Hydrodynamic Transfersupporting
confidence: 81%
“…23 Importantly, these properties are conferred without the need for virus-encoded proteins or selective pressure. 21,24 Mitotic stability appears to be provided by direct interaction of the S/MAR element with components of the nuclear matrix, 23,25 including the scaffold attachment factor A protein, which is the principal component of cellular chromatin and chromosomes. 26 Furthermore, this interaction probably brings the S/MAR plasmids into contact with the host replication machinery, which is located on the nuclear matrix, thereby facilitating replication once per cell cycle and hence extra-chromosomal stability.…”
Section: Introductionmentioning
confidence: 99%
“…19 The initial selection step, however, is critical to enrich the mitotically stable episomal plasmids in vitro, and lack of selective pressure results in less than 1% of replicating cells retaining the vector after 1 month. 7,20 Both in vitro and in vivo the stable attachment of S/MAR plasmid to the chromatin and its subsequent replication is a very rare event. S/MAR-plasmid attachment appears to require a reorganization of chromatin during cell division.…”
Section: Discussionmentioning
confidence: 99%